Preparation method of composite phase change energy storage material based on corncob / steel slag binary solid waste

By using corn cobs and steel slag to form a porous skeleton and mixing it with paraffin, the problems of easy leakage and poor thermal conductivity of phase change materials are solved, and the stability and thermal conductivity are improved, and there are broad application prospects.

CN119799285AActive Publication Date: 2025-04-11UNIV OF SCI & TECH BEIJING
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510017778.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

Existing phase change materials are prone to leakage during solid-liquid transformation, and have a low thermal conductivity, which affects the performance and safety of the heat storage system.

Method used

Corn core and steel slag are used as porous skeleton materials, and binary porous solid waste skeletons are formed through drying and carbonization, and paraffin is fully mixed with the skeleton materials as phase change material to form a stable composite phase change energy storage material.

Benefits of technology

The stability and thermal conductivity of phase change materials have been improved. The material has a stable shape and is not easy to leak, and has good thermal performance and cycling stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799285A_ABST
    Figure CN119799285A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite phase-change materials, and particularly relates to a preparation method of a corncob / steel slag binary solid waste-based composite phase-change energy storage material, which comprises the following steps: taking corncobs and steel slag as matrix raw materials, carrying out carbonization treatment on the corncobs to construct a porous network cross-linked carbon matrix, and carrying out high-temperature calcination treatment on the steel slag to reconstruct crystals, thereby obtaining the corncob / steel slag binary solid waste-based composite phase-change energy storage material. And mixing and co-sintering to prepare a binary solid waste framework. And loading the phase change material into the binary solid waste skeleton through an impregnation adsorption method to finally prepare the corncob / steel slag binary solid waste composite phase change energy storage material. The solid waste which is wide in source and low in cost is subjected to resource utilization, the porous structure of the solid waste composite phase change energy storage material has adsorption performance and heat conduction performance, and the prepared solid waste composite phase change energy storage material is excellent in heat storage performance, good in stability, not prone to leakage and wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite phase change materials, and in particular relates to a preparation method of a composite phase change energy storage material based on corn cob / steel slag binary solid waste. Background Art

[0002] With the continuous exploitation of fossil energy, environmental problems and resource depletion problems are becoming increasingly prominent. Phase change energy storage technology achieves energy storage and release through state changes, solving the time and space mismatch problems in the supply of new energy. However, phase change materials are prone to leakage during the solid-liquid transition process and have low thermal conductivity, which seriously affects the performance and safety of the heat storage system. The porous skeleton enhances the stability of the phase change material in the pores by virtue of its capillary effect and surface tension, while improving thermal conductivity, thermal stability and chemical stability. Exploring new composite phase change materials with low cost and strong thermal performance is an important research direction in this field.

[0003] Solid waste is formed into a unique porous structure through pretreatment and has a large specific surface area and adsorption performance, which provides a new idea for the preparation of composite phase change materials. Most of the current studies use a single type of solid waste skeleton material for preparation. For example, Chinese invention patent CN114890811A discloses a method for preparing porous phase change energy storage materials using mining solid waste. This technology mixes an organic foam with a mixture slurry of iron tailings, waste rock and additives, sinters the dried embryo, and discharges the organic foam at high temperature. The porous ceramic has high mechanical strength, but poor porosity, and the foaming pores decompose and release a large amount of CO2. Chinese invention patent CN113861946A discloses a method for preparing a lotus stem biomass porous carbon composite phase change material. A lotus stem porous carbon material is obtained by high-temperature carbonization in an argon atmosphere. The porous carbon material has a good pore structure and a high thermal conductivity. The bio-based skeleton has poor compressive and bending resistance, low mechanical strength, and a large thermal volume expansion coefficient that may cause rupture, so its practical application is limited.

[0004] Therefore, it is necessary for the present application to provide a method for preparing a composite phase change energy storage material based on corn cob / steel slag binary solid waste to solve the problems existing in the above-mentioned prior art. Summary of the invention

[0005] The purpose of the present invention is to effectively utilize industrial waste and agricultural waste as a porous skeleton to overcome the problems of easy leakage and poor thermal conductivity of phase change materials. A preparation method of a corn cob / steel slag binary solid waste composite phase change energy storage material is proposed. The solid waste composite phase change energy storage material prepared by this method has a stable shape and good thermal properties and cycle stability.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a composite phase change energy storage material based on a binary solid waste of corn cob / steel slag, wherein the composite phase change energy storage material comprises a binary porous solid waste skeleton mixed with a steel slag material and a corn cob carbon material and a phase change material located inside the porous skeleton, and the preparation method comprises the following steps:

[0008] Step 1: Slag pretreatment

[0009] Put the steel slag in a muffle furnace, calcine it at high temperature, cool it naturally to room temperature, and grind it into powdered steel slag material for later use;

[0010] Step 2: Corncob carbonization pretreatment

[0011] The crushed corn cobs are dried at a constant temperature to a constant weight, carbonized in a tube furnace according to a temperature increase mechanism, naturally cooled to room temperature, and finally ground into powder to obtain a corn cob carbon material sample for later use;

[0012] Step 3: Preparation of corncob / steel slag binary porous solid waste skeleton

[0013] The steel slag pretreatment material of step 1 and the corn cob carbon material of step 2 are weighed in a certain mass ratio, mixed, ground and co-sintered in a planetary ball mill to prepare a corn cob / steel slag binary porous solid waste skeleton;

[0014] Step 4: Preparation of corncob / steel slag binary solid waste composite phase change energy storage material

[0015] Weigh the corn cob / steel slag binary porous solid waste skeleton and paraffin prepared in step 3 according to a certain mass ratio, set a drying oven at a certain temperature to completely melt the paraffin, stir the mixed material at intervals to fully mix the paraffin and the skeleton material, and cool to room temperature; put the mixed and cooled sample into a mold and press it to obtain a corn cob / steel slag binary solid waste composite phase change energy storage material.

[0016] Furthermore, in step 1, the high temperature calcination temperature of the muffle furnace is 800° C.-900° C., the calcination time is 8-10 hours, and the particle size of the ground steel slag material is 200-300 mesh.

[0017] Furthermore, in step 2, the particle size of the crushed corn cobs is 2-5 cm, and argon gas is introduced at a flow rate of 300 mL / min for 30 minutes before the tubular furnace is heated to ensure that an inert atmosphere is formed inside the tubular furnace; the carbonization temperature is 400°C-500°C, the heating rate is 10°C / min, the insulation time is 60 minutes, and the reaction is naturally cooled to room temperature after the reaction is completed. During carbonization, the argon flow rate is adjusted to 100 mL / min.

[0018] Furthermore, in step 3, the mass ratio of the corn cob carbon material to the steel slag pretreated material is 2-4:1.

[0019] Furthermore, in step 3, the rotation speed of the planetary ball mill is 200 rpm, and the grinding time is 30 min.

[0020] Furthermore, in step 3, the co-sintering process of the corn cob carbon material and the steel slag pretreated material is a nitrogen gas flow rate of 200 mL / min, a heating rate of 5°C / min, and a co-pyrolysis at a temperature of 400°C-500°C for 1 hour.

[0021] Furthermore, in step 4, the mass ratio of the binary porous solid waste skeleton to paraffin is 1-2:1.

[0022] Furthermore, in step 4, the temperature of the drying oven is set to 50° C., stirring is performed every 30 minutes, and the total insulation time is 2 hours.

[0023] Furthermore, in step 4, the mold is a cylindrical mold, and the press is pressed at a pressure of 6 MPa for 3 minutes.

[0024] By adopting the above technical solution: using a mixture of corn cobs and steel slag with a porous structure as the raw material for preparing porous materials, the unique morphological characteristics and natural structure of corn cobs can form a cylindrical pore structure after drying and carbonization, providing sufficient storage space for phase change materials; steel slag has a certain compressive resistance, which makes up for the rupture of corn cobs caused by the volume expansion of phase change materials. The binary mixture of steel slag and corn cobs complements each other in terms of composition properties and morphological structure, and the composite phase change material prepared by using binary solid waste to replace the traditional packaging skeleton can not only achieve cross-temporal and spatial control of energy to improve energy utilization, but also reduce carbon emissions and environmental pollution caused by the skeleton production process, and promote the deep integration and circular development of multiple industries in the field of phase change energy storage and solid waste resource utilization.

[0025] From the above, compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The present invention uses agricultural solid waste corn cobs and industrial solid waste steel slag as skeleton materials to realize the resource utilization of industrial and agricultural solid waste, effectively reduce carbon emissions and environmental pollution from solid waste treatment, and the energy storage material composited with phase change materials has a stable shape and does not leak, promoting the deep integration and circular development of multiple industries in the field of phase change energy storage and resource utilization of solid waste.

[0027] 2. The present invention optimizes the pore structure of corn cobs and steel slag and effectively encapsulates the phase change material through adsorption impregnation. Experimental results show that the solid waste composite phase change energy storage material can adsorb 30% of paraffin, with a latent heat of 28.56 J / g and a thermal conductivity of 0.44 W / (m*K), and has good thermal performance and cycle stability.

[0028] 3. The present invention has a simple operation process, minimal capital investment, a short preparation cycle (24 hours), no need for large-scale instruments and equipment, and can achieve large-scale assembly line industrial production. The solid waste composite phase change energy storage material can be applied to thermal management fields such as heat dissipation of electronic devices, and has broad application prospects.

[0029] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description in combination with the preferred embodiments and the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.

[0031] Figure 1 This is a SEM image of the corncob carbon material of the present invention;

[0032] Figure 2 This is a SEM image of the corncob / steel slag binary solid waste composite phase change energy storage material of the present invention;

[0033] Figure 3 This is a macroscopic physical picture of the corncob / steel slag binary solid waste composite phase change energy storage material of the present invention;

[0034] Figure 4 This is a differential scanning calorimetry curve of the corncob / steel slag binary solid waste composite phase change energy storage material of the present invention;

[0035] Figure 5 This is a comparison diagram of the macroscopic characterization of the composite phase change materials with corn cob / steel slag, corn cob, and steel slag as the skeleton of the present invention. DETAILED DESCRIPTION

[0036] The following is a detailed description of the specific embodiments of the present invention in conjunction with the accompanying drawings, which is a part of this specification and illustrates the principles of the present invention through examples. Other aspects, features and advantages of the present invention will become clear from the detailed description. In the referenced drawings, the same or similar components in different figures are represented by the same reference numerals.

[0037] Example 1

[0038] A preparation method of a corncob / steel slag binary solid waste composite phase change energy storage material, comprising the following steps:

[0039] (1) Place the crushed corn cobs with a particle size of 2 to 5 cm in a 105°C constant temperature drying oven and dry for 48 hours. After cooling, weigh 10 g of corn cobs and place them in a tube furnace. Heating the temperature at a rate of 10°C / min to a carbonization temperature of 500°C, carbonize for 60 minutes, and then naturally cool to room temperature after stopping heating. Grind the powder to a particle size of 200 mesh to obtain a corn cob carbon material sample.

[0040] (2) Take 10 g of steel slag and place it in a muffle furnace, calcine it at 900°C for 8 h, cool it naturally to room temperature, and grind it into a powder with a particle size of 200 mesh.

[0041] (3) Weigh 1g corn cob carbon material and 1g steel slag, grind them in a planetary mill at 200 rpm for 20 minutes. After mixing and grinding, place them in a tube furnace and heat them to 500℃ at a heating rate of 5℃ / min in a nitrogen atmosphere (N2 flow rate is 200mL / min) for pyrolysis for 1h. After cooling, grind them in a planetary mill at 200 rpm for 20 minutes to obtain a binary solid waste skeleton material.

[0042] (4) Weigh 1g of binary solid waste skeleton material and 1g of paraffin wax in a beaker and mix them. Place them in a 50°C drying oven and keep them warm for 2 hours to completely melt the liquefied paraffin wax. Stir once every 30 minutes to fully mix the paraffin wax and binary solid waste skeleton material. Cool to room temperature. Place the mixed and cooled sample in a cylindrical mold and press it at 6MPa for 3 minutes using a press to obtain a corn cob / steel slag binary solid waste composite phase change energy storage material.

[0043] (5) The prepared corncob / steel slag binary solid waste composite phase change energy storage material was placed in a 50°C drying oven to remove the phase change material on the surface or not adsorbed into the pores. The filter paper was replaced continuously to ensure that there was no leakage of liquid phase change material.

[0044] The corncob carbon material prepared in Example 1 was characterized by scanning electron microscopy. Figure 2 As shown in the figure, carbonized corncob forms a three-dimensional multi-porous structure; the scanning electron microscopy test characterization of corncob / steel slag solid waste composite phase change energy storage material is shown in the figure. Figure 3 As shown in Figure 2, the pores are fully occupied after paraffin adsorption. Differential scanning calorimetry (DSC) was used to characterize the corncob / steel slag solid waste composite phase change energy storage material. Figure 4 As shown, the phase change temperature is 28.56℃, the phase change enthalpy is 32.24J / g, and it has good heat storage performance; the thermal conductivity of pure paraffin and corn cob / steel slag solid waste composite phase change energy storage material measured at room temperature by thermal constant analyzer is 0.21W / (m*K) and 0.44W / (m*K). Steel slag and corn cob as porous skeletons have an improvement effect on the thermal conductivity of phase change materials.

[0045] Comparative Example 1

[0046] The preparation method of the composite phase change energy storage material based on corncob solid waste described in this comparative example consists of the following steps:

[0047] (1) Place the crushed corn cobs with a particle size of 2 to 5 cm in a 105°C constant temperature drying oven and dry for 48 hours. After cooling, weigh 10 g of corn cobs and place them in a tube furnace. Heating the temperature at a rate of 10°C / min to a carbonization temperature of 500°C, carbonize for 60 minutes, and then naturally cool to room temperature after stopping heating. Grind the powder to a particle size of 200 mesh to obtain a corn cob carbon material sample.

[0048] (2) Weigh 1g corncob carbon material and 1g paraffin wax in a beaker and mix them. Place them in a 50℃ drying oven and keep them warm for 2h to completely melt the liquefied paraffin wax. Stir every 30min to fully mix the paraffin wax and corncob carbon material. Cool to room temperature. Place the mixed and cooled sample in a cylindrical mold and press it at 6MPa for 3min using a press (MSY-50) to obtain a corncob composite phase change energy storage material.

[0049] Comparative Example 2

[0050] The preparation method of the composite phase change energy storage material based on steel slag solid waste described in this comparative example consists of the following steps:

[0051] (1) Take 10 g of steel slag and place it in a muffle furnace, calcine it at 900°C for 8 h, cool it naturally to room temperature, and grind it into a powder with a particle size of 200 mesh.

[0052] (2) Weigh 1g of steel slag and 1g of paraffin wax in a beaker and mix them. Place them in a 50℃ drying oven and keep them warm for 2h to completely melt the liquefied paraffin wax. Stir every 30min to fully mix the paraffin wax and steel slag materials. Cool them to room temperature. Place the mixed and cooled samples in a cylindrical mold and press them at 6MPa for 3min using a press (MSY-50) to obtain a steel slag composite phase change energy storage material.

[0053] The composite phase change energy storage materials of Example 1, Comparative Example 2 and Comparative Example 3 were macroscopically characterized using a digital camera. The results are as follows: Figure 5 As shown, it shows that the corn cob / steel slag binary solid waste composite phase change energy storage material has a stable structure and can prevent the leakage of phase change materials.

[0054] In summary, the present invention utilizes solid waste with a wide range of sources and low cost. Its porous structure has adsorption and thermal conductivity properties. The solid waste composite phase change energy storage material prepared by the present invention has excellent thermal storage performance, good stability and is not prone to leakage, and has broad application prospects.

[0055] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.

Claims

1. A method for preparing a corncob / steel slag binary solid waste composite phase change energy storage material, characterized in that: The composite phase change energy storage material comprises a binary porous solid waste skeleton mixed with steel slag material and corn cob carbon material and a phase change material located inside the porous skeleton. The preparation method comprises the following steps: Step 1: Slag pretreatment Put the steel slag in a muffle furnace, calcine it at high temperature, cool it naturally to room temperature, and grind it into powdered steel slag material for later use; Step 2: Corncob carbonization pretreatment The crushed corn cobs are dried at a constant temperature to a constant weight, carbonized in a tube furnace according to a temperature increase mechanism, naturally cooled to room temperature, and finally ground into powder to obtain a corn cob carbon material sample for later use; Step 3: Preparation of corncob / steel slag binary porous solid waste skeleton The steel slag pretreatment material of step 1 and the corn cob carbon material of step 2 are weighed in a certain mass ratio, mixed, ground and co-sintered in a planetary ball mill to prepare a corn cob / steel slag binary porous solid waste skeleton; Step 4: Preparation of corncob / steel slag binary solid waste composite phase change energy storage material Weigh the corn cob / steel slag binary porous solid waste skeleton and paraffin prepared in step 3 according to a certain mass ratio, set a drying oven at a certain temperature to completely melt the paraffin, stir the mixed material at intervals to fully mix the paraffin and the skeleton material, and cool to room temperature; put the mixed and cooled sample into a mold and press it to obtain a corn cob / steel slag binary solid waste composite phase change energy storage material.

2. The method for preparing a corncob / steel slag binary solid waste composite phase change energy storage material according to claim 1, characterized in that: In step 1, the high-temperature calcination temperature of the muffle furnace is 800° C.-900° C., the calcination time is 8-10 hours, and the particle size of the ground steel slag material is 200-300 meshes.

3. The method for preparing a corncob / steel slag binary solid waste composite phase change energy storage material according to claim 1, characterized in that: In step 2, the crushed corn cob has a particle size of 2-5 cm, and argon gas is introduced at a flow rate of 300 mL / min for 30 minutes before the tubular furnace is heated to ensure that an inert atmosphere is formed inside the tubular furnace; the carbonization temperature is 400°C-500°C, the heating rate is 10°C / min, the insulation time is 60 minutes, and the reaction is naturally cooled to room temperature after the reaction is completed. During carbonization, the argon flow rate is adjusted to 100 mL / min.

4. The method for preparing a corncob / steel slag binary solid waste composite phase change energy storage material according to claim 1, characterized in that: In step 3, the mass ratio of the corn cob carbon material to the steel slag pretreatment material is 2-4:

1.

5. The method for preparing a corncob / steel slag binary solid waste composite phase change energy storage material according to claim 1, characterized in that: In step 3, the rotation speed of the planetary ball mill is 200 rpm, and the grinding time is 30 min.

6. The method for preparing a corncob / steel slag binary solid waste composite phase change energy storage material according to claim 1, characterized in that: In step 3, the co-sintering process of the corn cob carbon material and the steel slag pretreated material is a nitrogen gas with a flow rate of 200 mL / min, a heating rate of 5°C / min, and a co-pyrolysis at a temperature of 400°C-500°C for 1 hour.

7. The method for preparing a corncob / steel slag binary solid waste composite phase change energy storage material according to claim 1, characterized in that: In step 4, the mass ratio of the binary porous solid waste skeleton to paraffin is 1-2:

1.

8. The method for preparing a corncob / steel slag binary solid waste composite phase change energy storage material according to claim 1, characterized in that: In step 4, the temperature of the drying oven is set to 50° C., stirring is performed every 30 minutes, and the total insulation time is 2 hours.

9. The method for preparing a corncob / steel slag binary solid waste composite phase change energy storage material according to claim 1, characterized in that: In step 4, the mold is a cylindrical mold, and the press is pressed at a pressure of 6 MPa for 3 minutes.

Citation Information

Patent Citations

  • Lotus root stalk biomass porous carbon composite phase change material and preparation method thereof

    CN113861946A

  • Porous phase change energy storage material prepared from mine solid waste and method

    CN114890811A

  • Multi-element matrix composite phase-change energy-storage material and preparation method thereof

    CN109837069A

  • Preparation method and application of biochar-steel slag composite adsorption material

    CN114669268A

  • Preparation method and application of hydrothermal carbon co-pyrolysis adsorption material

    CN118217958A